1995
DOI: 10.1084/jem.181.1.363
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric identification of a naturally processed melanoma peptide recognized by CD8+ cytotoxic T lymphocytes.

Abstract: SutnlmaryWe and others have previously reported that melanoma-specific, cytotoxic T lymphocytes (CTL) define a minimum of six class I-presented peptide epitopes common to most HLA-A2 + melanomas. Here we show that three of these peptide epitopes are coordinately recognized by a CTL clone obtained by limiting dilution from the peripheral blood of an HLA-A2 + melanoma patient. Tandem mass spectrometry was used to characterize and sequence one of these three naturally processed melanoma peptides. One of the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(86 citation statements)
references
References 35 publications
(47 reference statements)
1
83
0
Order By: Relevance
“…28 Third, the Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope is generated and presented by HLA-A2 ϩ melanoma cells, and these are efficiently lysed by Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2-specific CTLs. 29 Finally, the Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope is generated by conventional proteasomes but may be destroyed by immunoproteasomes expressed by DCs or by interferon-␥ (IFN-␥)-treated tumor cells. 30 This final point makes the development of a Melan-A protein vaccine problematic as immunoproteasome-expressing DCs will fail to generate tumor-relevant CTLs in vivo, thus restricting the development of a Melan-A vaccine to peptide-based strategies, which have shown limited clinical efficacy because of multiple tumor escape mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Third, the Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope is generated and presented by HLA-A2 ϩ melanoma cells, and these are efficiently lysed by Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2-specific CTLs. 29 Finally, the Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope is generated by conventional proteasomes but may be destroyed by immunoproteasomes expressed by DCs or by interferon-␥ (IFN-␥)-treated tumor cells. 30 This final point makes the development of a Melan-A protein vaccine problematic as immunoproteasome-expressing DCs will fail to generate tumor-relevant CTLs in vivo, thus restricting the development of a Melan-A vaccine to peptide-based strategies, which have shown limited clinical efficacy because of multiple tumor escape mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…26 In contrast, Melan-A is unusual. First, a large proportion of healthy human leukocyte associated-A2 (HLA-A2)-restricted individuals possess naive CD8 ϩ T cells specific for the naturally presented Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope. 27 Second, the Melan-A [26][27][28][29][30][31][32][33][34][35] /HLA-A2 epitope is strikingly immunodominant with few other CD8 ϩ T-cell epitopes described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Because massive numbers of tumor cells and CTL are needed for this technique, however, it remained unpublished for pancreatic cancer. This problem might be circumvented by utilizing mice for establishing new pancreatic cancer cell lines, though sufficient experience with pancreatic cancer cells makes the establishment of new cell lines easier.…”
Section: Hla-a2 Is 1 Restriction Element In Recognition Of Pancreaticmentioning
confidence: 99%
“…To date, with the exception of melanoma (Castelli et al, 1996;Cox et al, 1994), there is limited information on the intrinsic immunogenicity or the identity and density of antigenic peptides and CTL epitopes presented by the majority of spontaneously arising human tumours. However, in the last few years several reports have shown that multiple epitopes can be recognized by T cells on several human tumours (i.e.…”
mentioning
confidence: 99%